Silencing of OsGRXS17 in rice improves drought stress tolerance by modulating ROS accumulation and stomatal closure. Issue 1 (December 2017) - Hu, Ying; Wu, Qingyu; Peng, Zhao; Sprague, Stuart; Wang, Wei; Park, Jungeun; Akhunov, Eduard; Jagadish, Krishna; Nakata, Paul; Cheng, Ninghui; Hirschi, Kendal; White, Frank; et al.
Abstract Glutaredoxins (GRXs) modulate redox-dependent signaling pathways and have emerged as key mediators in plant responses to environmental stimuli. Here we report that RNAi-mediated suppression ofOryza sativa GRXS17 (OsGRXS17 ) improved drought tolerance in rice. Gene expression studies showed thatOsGRXS17 was present throughout the plant and that transcript abundance increased in response to drought stress and abscisic acid (ABA) treatment. Localization studies, utilizing GFP-OsGRXS17 fusion proteins, indicated that OsGRXS17 resides in both the cytoplasm and the nuclear envelope. Under drought stress conditions, rice plants with reducedOsGRXS17 expression showed lower rates of water loss and stomatal conductance, higher relative water content, and enhanced survival compared to wild-type controls. Further characterization of theOsGRXS17 down-regulated plants revealed an elevation in H2 O2 production within the guard cells, increased sensitivity to ABA, and a reduction in stomatal apertures. The findings demonstrate a critical link between OsGRXS17, the modulation of guard cell H2 O2 concentrations, and stomatal closure, expanding our understanding of the mechanisms governing plant responses to drought.